Rola cytokin i chemokin w odpowiedzi zapalnej - Harvanová, Gabriela; Duranková, Silvia; Bernasovská, Jarmila (Alergologia Polska - Polish Journal of Allergology, 2023)
All organisms are interconnected through the processes and relationships that take place within them. It is the interdependence of organs that forms the overall complex. In the course of evolution, the immune system in some species has been refined. However, in the event of allergy or foreign body penetration, serious damage can occur. The immune system is a barrier that provides organisms with protection from both external and internal influences. The body’s immune response is one of the most basic and important functions of the human body. When seemingly harmless antigens of a chemical or biological nature enter the body, the immune system activates antibodies to prevent the antigen from multiplying in the body. As part of inflammation, the immune system is mobilized, with immune cells detecting the degree and severity of damage to blood vessels and the lymphatic system. Subsequently, the allergen is cleared or prevented from spreading through the response of immunocompetent cells.